CORRIGENDUM FOR 10.1210/en.2012-2130 (Endocrinology, 2016)
CONTEXT: Adrenarche involves maturation of the adrenal zona reticularis (ZR), but its molecular regulation is poorly understood. MicroRNAs (miRNAs) may contribute to adrenal development. OBJECTIVE: To investigate whether circulating miRNAs are associated with ZR maturation during adrenarche and to characterize the functional role of candidate miRNAs in adrenal steroidogenesis. DESIGN AND SETTING: Prospective cohort study was nested within the population-based PANIC study with longitudinal follow-up at ages 7, 9, and 15 years, combined with experimental analyses in the human adrenocortical NCI-H295R cell model. PARTICIPANTS: A total of 34 children (20 girls) with clinical and/or biochemical signs of adrenarche at age 9 as cases, and 24 age-matched controls (11 girls). INTERVENTIONS: None. MAIN OUTCOME MEASURES: Longitudinal serum miRNA expression and in vitro effects of candidate miRNAs on adrenal steroidogenesis and gene expression. RESULTS: Serum miR-1-3p levels were higher in cases compared to controls at age 7 years (fold change 2, p < 0.001), preceding clinical adrenarche. In both groups, miR-1-3p levels declined during adrenarchal and pubertal development. In vitro, miR-1-3p overexpression increased steroidogenic activity (approximately 1.5-fold on average) without altering the expression of canonical steroidogenic enzyme genes. Transcriptomic analysis identified 208 upregulated and 140 downregulated genes, including PRKCA, encoding protein kinase C (PKC), enriched in the ZR and involved in steroidogenic signaling. CONCLUSIONS: Elevated circulating miR-1-3p precedes clinical adrenarche and enhances steroidogenesis in vitro. The temporal decline of circulating miR-1-3p levels and the identification of PKC support a model in which miR-1-3p may contribute to functional maturation of the ZR through modulation of non-canonical intracellular signaling pathways.